Parallel Monte Carlo computations in SCore environment - Vošterienė, Svajonė (Lietuvos matematikos rinkinys, 2004)
Parallel Monte Carlo (PMC) methods are successful because particles are typically independent and easily distributed to multiple processors. We use the PC Cluster TAURAS [1] with the SCore cluster system software on top of Linux OS to present the strategy for parallelizing Monte Carlo calculations. The cluster help us to generate parallel random numbers for simulating our task and to computerize parallel programs. In this particle we present the PMC, who let us simulate the mortar firing. We propose computations that are very effective because the digital experiment can substitute costly firings at the shooting range, the pollution of the environment is reduced, etc.